Standards of practice in acute ischemic stroke intervention: international recommendations - Pierot, Laurent; Hacke, Werner (Journal of neuroInterventional surgery, 2018)
After the five positive randomized controlled trials showing the benefit of mechanical thrombectomy (MT) in the management of acute ischemic stroke (AIS) with emergent large vessel occlusion (ELVO), a multisociety meeting was organized during the 16th Congress of the World Federation of Interventional and Therapeutic Neuroradiology (WFITN), October 2015, Gold Coast (Australia). This meeting was dedicated to the training of physicians performing MT, and recommendations were published thereafter in multiple scientific journals. The same group of scientific societies decided to organize a similar meeting during the 17th WFITN Congress, October 2017, Budapest (Hungary). This multisociety meeting was dedicated to standards of practice in acute ischemic stroke intervention (AISI), aiming for a consensus on the minimum requirements for centers providing such treatment. In an ideal situation, all patients would be treated at a center offering a full spectrum of neuroendovascular care (a level 1 center). However, for geographical reasons, some patients are unable to reach such a center in a reasonable period of time. With this in mind, the group paid special attention to define recommendations on the prerequisites of organizing stroke centers providing MT for AIS, but not for other neurovascular diseases (a level 2 center). Finally, some centers will have a stroke unit and offer intravenous thrombolysis, but not any endovascular stroke therapy (a level 3 center). Together, these level 1, 2, and 3 centers form a complete stroke system of care. The requirements for these centers are summarized in table Due to the relatively short time elapsed since the evidence in favor of MT has been published, some organizational aspects still require scientific validation. However, considering the extremely fast growth of such activities around the world, the multisociety group considered it timely and rational to set-up recommendations and a framework for the development of MT services in all parts of the world. The requirements included in this document are proposed to help countries and centers to properly implement MT.